Introduction to Laser Technology - Hitz, C. Breck, author 551358; Ewing, J. J. (James J.), 1942-, author 551359; Hecht, Jeff author 299387 (Hoboken, N.J. : Wiley-IEEE Press, 2012)
"This new edition includes a new chapter on fiber lasers, and a discussion of arrays in the semiconductor chapter. It also includes new end of chapter problems"--